Detached Anterior Horn of the Medial Meniscus Mimicking a Parameniscal Cyst. (15th October 2015) - Fukuta, Shoji; Tsutsui, Takahiko; Matsuura, Tetsuya; Suzue, Naoto; Hamada, Daisuke; Goto, Tomohiro; Sairyo, Koichi
Abstract : We report a case of a detached anterior horn of the medial meniscus with anterior knee pain. Preoperative magnetic resonance images of the knee were initially interpreted as a parameniscal cyst. Arthroscopic examination revealed subluxation of the anterior horn of the medial meniscus due to detachment from its anterior tibial insertion. Arthroscopic fixation with a suture anchor was successful and the cystic lesion was no longer visible on postoperative images.